Cybersecurity for commercial vehicles - D'Anna, Gloria D. (Cybersecurity series., 2019)
This book provides a thorough view of cybersecurity to encourage those in the commercial vehicle industry to be fully aware and concerned that their fleet and cargo could be at risk to a cyber-attack. It delivers details on key subject areas including: * SAE International Standard J3061; the cybersecurity guidebook for cyber-physical vehicle systems * The differences between automotive and commercial vehicle cybersecurity. * Forensics for identifying breaches in cybersecurity. * Platooning and fleet implications. * Impacts and importance of secure systems for today and for the future. Cybersecurity for all segments of the commercial vehicle industry requires comprehensive solutions to secure networked vehicles and the transportation infrastructure. It clearly demonstrates the likelihood that an attack can happen, the impacts that would occur, and the need to continue to address those possibilities. This multi-authored presentation by subject-matter experts provides an interesting and dynamic story of how industry is developing solutions that address the critical security issues; the key social, policy, and privacy perspectives; as well as the integrated efforts of industry, academia, and government to shape the current knowledge and future cybersecurity for the commercial vehicle industry.